Effects of Soil Parent Material and Climate on the Performance of Vitis vinifera L. cvs. Sauvignon blanc and Cabernet Sauvignon - Part I. Soil Analysis, Soil Water Status, Root System Characteristics, Leaf Water Potential, Cane Mass and Yield - Shange, L.P.; Conradie, W.J. (South African Journal of Enology and Viticulture, 2016)
In the Helderberg area of the Western Cape, South Africa, soil parent material may vary between granite and shale over relatively short distances. However, little information is available concerning the possible effects of different soil parent materials on grapevine performance. A five-year investigation (2004/05 to 2008/09) was therefore carried out. Two Sauvignon blanc and two Cabernet Sauvignon vineyard blocks were selected at four localities. Soils derived mainly from granite and shale were identified in each vineyard block. Climate and soil parameters, root distribution, grapevine water status, cane mass and yield were evaluated at all localities. Shale-derived soils contained significantly greater amounts of fine sand, but less coarse sand, than granite-derived soils. These differences resulted in water-holding capacities that were generally higher in the shale-derived soils. Shale-derived soils contained higher concentrations of total potassium (K), but the levels of water-soluble K were generally greater in the granitic soils. Root system development could not be related directly to soil parent material. However, in most cases fine root density in the granite-derived soils tended to be higher, while the cane mass and yield of grapevines in the same soils also tended to be higher, at least at two of the four localities. The effect of soil parent material on grapevine water constraints seemed more prominent during the drier seasons, namely 2004/05 and 2005/06, compared to the wet and coolest seasons, 2007/08 and 2008/09.